Identification of sensory attributes, instrumental and chemical measurements important for consumer acceptability of grilled lamb Longissimus lumborum. (February 2015) - Oltra, O.R.; Farmer, L.J.; Gordon, A.W.; Moss, B.W.; Birnie, J.; Devlin, D.J.; Tolland, E.L.C.; Tollerton, I.J.; Beattie, A.M.; Kennedy, J.T.; Farrell, D.
Abstract: In this study, important eating quality attributes that influence consumer liking for grilled lamb loin have been identified using preference mapping techniques. The eating quality attributes identified as driving the consumer liking of lamb loin steaks were "tenderness", "sweet flavour", "meaty aftertaste", "roast lamb flavour" and "roast lamb aftertaste". In contrast, the texture attribute "rubbery" and the flavour attributes "bitter flavour" and "bitter aftertaste" had a negative influence on consumer perceptions. Associations were observed between eating quality and a number of instrumental and chemical measurements. Warner Bratzler Shear Force showed an association with "rubbery" texture and a negative association with "tenderness" and consumer liking scores. The compounds, glucose, glucose-6-phosphate, inosine, inosine monophosphate and adenosine monophosphate were associated with the attributes, "sweet flavour", "meaty aftertaste", "roast lamb flavour", "roast lamb aftertaste" and with consumer scores for liking of lamb which is probably caused by the role some of these compounds play as precursors of flavour and as taste compounds. Highlights: Eating quality attributes driving consumer liking of lamb were identified. Consumer clusters were differentiated by sensory but not demographic factors. Associations were observed between instrumental measurements and eating quality. Links shown between flavour precursors, sensory attributes and consumer scores